Function of Nitrate Ion and Tea Saponin Application Rates in Anerobic PAH Dissipation in Paddy Soil. Issue 6 (16th February 2016) - Sun, Mingming; Ye, Mao; Shen, Fangyuan; Xu, Jingjing; Ye, Chenglong; Yu, Li; Hu, Feng; Li, Huixin; Jiang, Xin; Kengara, Fredrick Orori
Abstract : In the present study, KNO3 and tea saponin (TS) were applied to investigate systematically the potential impact of their concentrations on dissipation of anerobic polycyclic aromatic hydrocarbons (PAH) in paddy soils. After 150 days of incubation, the highest removals for total, 3‐, 4‐, and 5(+6)‐ring PAHs were 84.3, 92.3, 85.6, and 69.3%, respectively, with the simultaneous application of 50 mM KNO3 and 2% TS, w/w. Moreover, using response surface methodology, the theoretical maximum removal for total PAHs in the 80–100% range can be achieved at >35 mM KNO3 and >1.5% TS, w/w. Meanwhile, Tenax ® TA extraction and a first‐three‐compartment model method demonstrated that TS (w/w, 2%) could serve as an effective bioaccessibility‐enhancing agent to increase the rapidly and slowly desorbing fractions of PAHs from 6 and 12% in the control to 29 and 42% ( p < 0.05), respectively. In addition, proper concentrations of KNO3 and TS in soil could enhance soil microbial characteristics, including denitrifying bacterial count, nitrate reductase activity, and soil microbial biomass carbon and nitrogen, suggesting at least the partial restoration of microbial biological function to the soil after remediation. The results are important in understanding the anerobic PAH dissipation in paddy soils. Abstract : Application of KNO3 and tea saponin was effective in enhancing dissipation of polycyclic aromatic hydrocarbons in anerobic paddy soils. The combined treatment also contributed to the restoration of the microbial biological functioning of the contaminated soil.